Assessing the impact of the belt and road initiative, (BRI) on China-Malaysian economic and trade relations - Huayan, Niu; Adnan, Zatul Himmah; Md. Nor, Mohd Sabri; Mohd Zain, Mohd Izani (Faculty of Human Ecology, Universiti Putra Malaysia, 2023)
This article briefly assesses the effects of the 'Belt and Road Initiative' (BRI) on the economic and trade relations between China and Malaysia. This study utilized the qualitative method by reviewing selected literature and employing content analysis. The literature review examines various documents and articles on the economic and trade cooperation between Malaysia and China, specifically focusing on the 'BRI.' Using a SWOT-PEST analysis, this paper offers an understanding of the impact of the relations through the strengths and weaknesses from the political, economic, social, and technological dimensions. It is hoped to make a scholarly contribution towards the sustained expansion of economic and trade ties between China and Malaysia within the BRI framework. The analysis shows that, within the context of the "BRI," China and Malaysia exhibit robust political trust, stable economic relations, extensive societal exchanges, and substantial technological collaboration, creating an environment conducive to cooperation. However, challenges like trade imbalances, non-tariff barriers, domestic political shifts, international competitive interference, ecological repercussions, and data security threats require coordinated responses. However, with some comprehensive strategy and constructive measures, China and Malaysia can work well together for a better and more progressive achievement of the BRI in the future.